Finnish University Students' Views on Climate Change Education and Their Own Ability to Act as Climate Educators - Eija Yli-Panula; Eila Jeronen; Salla Koskinen; Sanna Mäki (MDPI AG, 2022)
Climate change (CC) has widespread impacts on human and natural systems and thus threatens the future of contemporary youths. Only a few studies on climate change education (CCE) have been published in Finland, and no research has been conducted on upper secondary education. Thus, this study investigated Finnish university students' views on CCE in upper secondary schools. According to them, the most common goals in CCE are increasing and structuring knowledge, developing thinking skills, and encouraging action both today and in the future. The respondents considered preconceived notions and opinions stemming from their inner circles, the media, and social debate to be the most difficult factor in teaching about CC. CCE was perceived to provide either a weak or relatively weak capacity to follow a climate-friendly lifestyle. By increasing and diversifying teaching and strengthening multidisciplinarity, climate-friendly lifestyles can be improved. The respondents' views on current and future CCE differed most clearly concerning motivation and inclusion, which are not prevalent in contemporary teaching. The results indicate, however, that the university students were motivated to increase and develop CCE, and according their answers, their own capacity to address different aspects of CCE was relatively good.